Melatonin in Assisted Reproductive Technology: A Pilot Double-Blind Randomized Placebo-Controlled Clinical Trial - Fernando, Shavi; Wallace, Euan Morrison; Vollenhoven, Beverley; Lolatgis, Nicholas; Hope, Nicole; Wong, Melissa; Lawrence, Mark; Lawrence, Anthony; Russell, Chris; Leong, Kenneth; Thomas, Philip; Rombauts, Luk (Frontiers in Endocrinology, 2018)
Purpose: To explore in a small pilot study whether oral melatonin, administered during ovarian stimulation increases clinical pregnancy rate (CPR) after IVF and what dose might be most effective. Methods: Pilot double-blind, dose-finding, placebo-controlled randomised clinical trial in private IVF clinics in Australia between September 2014 and September 2016. 160 women having their first cycle of IVF or ICSI were randomised to receive placebo (n=40), melatonin 2mg (n=41), melatonin 4mg (n=39) or melatonin 8mg (n=40) twice per day (BD) during ovarian stimulation. The primary outcome was CPR. Secondary outcomes included serum and follicular fluid (FF) melatonin concentrations, oocyte/embryo quantity/quality and live birth rate (LBR). Analysis was performed using the intention-to-treat principle. Results: There was no difference in CPR or LBR between any of the four groups (p=0.5). When all the doses of melatonin were compared as a group with placebo, the CPR was 21.7% for the former and 15.0% for the latter (OR 1.57 (95% CI 0.59, 4.14), p=0.4). There were also no differences between the groups in total oocyte number, number of MII oocytes, number of fertilised oocytes, or the number or quality of embryos between the groups. This is despite mean FF melatonin concentration in the highest dose group (8mg BD) being 9-fold higher compared with placebo (P < 0.001). Conclusion: No significant differences were observed in CPR or oocyte and embryo parameters despite finding a 9-fold increase in FF melatonin concentration. However, this study was not sufficiently powered to assess differences in CPR and therefore, these results should be interpreted with caution. A. Because this was a small RCT, a beneficial effect of melatonin on IVF pregnancy rates cannot be excluded and merits confirmation in further, larger clinical trials. ANZCTR (http://www.anzctr.org.au/ Project ID: ACTRN12613001317785).